Urticaria Diagnosis and Management - Papakonstantinou, Eleni (IntechOpen, 2021)
This book presents the most current knowledge in the diagnosis and management of urticaria. It also examines the scientific aspects of currently available treatments as well as potential new options for managing severe forms of the disease. Written by international experts in the field, the book addresses those aspects of diagnosing and treating urticaria important for physicians in various specialties, including dermatology, allergy, internal medicine, and more.